Report of Working Group on Coal and Lignite for the Eighth Five Year Plan (1990-95) - Planning Commission (Planning Commission, 1990)
In its first meeting held on 1st September 1988 the Working Group decided that Shri R.K.Sachdev, Director (Tech), Department of Coal will act as the Member-Secretary of the Working Group. A Co-ordination Committee comprising of Chairman of the Working Group, Chairmen of five Sub-Groups and the Member-Secretary was also set up to monitor the progress of work of various Sub-Groups. Shri R.S.Sane, Joint Secretary & Financial Adviser, Deptt. of Coal was co-opted as member of the Working Group as well as of Sub-Group V. Other Sub-Groups were advised to Co-opt members from certain organisations for facilitating the working of the Sub-Groups.
Govt of India Ministry of Energy Department of Coal
Govt of India Ministry of Energy Department of Coal